Gay Fathers, Their Children, and the Making of Kinship - Goodfellow, Aaron (Book collections on Project MUSE., 2015)
"Gay Fathers, Their Children and the Making of Kinship' explores the status of fatherhood when paternity can no longer be tied to procreative sex. It addresses how the anxiety associated with securing the paternal relation is assuaged when the biological anchors that commonly assure paternity are not readily available"--